Learning Karawitan Art Practice in Sidakarya Village | Pembelajaran Praktek Seni Karawitan di Desa Sidakarya - I Nyoman Diouf Saputra (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
The Thematic Real Work Lecture (KKNT) activities are held in Sidakarya Village; this activity lasts for 1 (one) semester or around 4 (four) months. The movement began with a thank you at Mutering Jagat Dalem Sidakarya Temple with all KKNT members. Then, the formation of the regeneration of Sidakarya Village, which children from grade 3 elementary school attended to grade 1 junior high school, totalling 32 (thirty-two) people from various hamlets in Sidakarya Village, was carried out at Mutering Jagat Dalem Temple Sidakarya with the material provided was Gending Petopeng is a basic gending that refers to the tabuh gilak in performing arts such as masks. The Implementation Method used in implementing the KKNT activities consists of Implementation Stages, Types of Activities, Implementation Patterns, and Outcomes. This implementation method is carried out through collecting field observation data, interviews, and documentation. The results obtained from this activity are that it is hoped that the drummers will be able to play the gamelan well and master the material that has been given as well as an external form for preparing for the Ngusaba Nini, Ngusaba Desa and Nangkluk Merana ceremonies in Sidakarya Village and the creation of Tabuh Gilak works as an outward form of a sense of devotion village writer.